Media Dissemination of the Montreal Cognitive Assessment After President Donald Trump’s Medical Evaluation - Haghbayan, Hourmazd (JAMA Neurol, 2018)
This study presents data on the surge in interest in the Montreal Cognitive Assessment in the wake of news about US President Donald Trump undergoing this test.